2009
DOI: 10.3109/15376510903452941
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption acceleration and calcium reabsorption impairment in a Thai population with high cadmium exposure

Abstract: Some residents of the Mae Sot district in Thailand have suffered long-term exposure to elevated dietary levels of cadmium. To test the hypothesis that chronic dietary cadmium exposure can cause imbalance in calcium dynamics and accelerate bone resorption, a group of these residents (156 men and 256 women aged >/= 50) were selected on the basis of previous records of elevated urinary cadmium and tested for urinary and blood cadmium, bone formation and resorption markers, and the renal tubular dysfunction marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…This is supported by a study of residents in Thailand with elevated urinary Cd, where the fractional excretion of calcium increased with rising cadmium exposure (urinary Cd) especially in women [28]. In that study, there was also a positive correlation between fractional calcium excretion and the excretion of bone resorption markers, and the levels of those markers were significantly higher in women.…”
Section: Discussionmentioning
confidence: 65%
“…This is supported by a study of residents in Thailand with elevated urinary Cd, where the fractional excretion of calcium increased with rising cadmium exposure (urinary Cd) especially in women [28]. In that study, there was also a positive correlation between fractional calcium excretion and the excretion of bone resorption markers, and the levels of those markers were significantly higher in women.…”
Section: Discussionmentioning
confidence: 65%
“…Increased urinary excretion of Ca was reported to be associated with increased Cd in the kidney in women [18], suggesting Cd exposure may influence bone metabolism mainly through increased Ca excretion into the urine in women. In residents aged ≥ 50 years in the same population, Nambunmee et al [10] reported that FECa, which increased with increased urinary Cd, was closely associated with an increase in urinary NTx, particularly in women. In the female participants in the current study, the prevalence of bone metabolic disorders based on a urinary NTx level ≥ 89.0 (nM BCE/mM Crea) was high, more than 25%, but only FECa was significantly associated with the prevalence of bone metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Swaddiwudhipong et al [9] reported that increased serum creatinine (Crea) and decreased glomerular filtration rate was associated with increased urinary Cd in inhabitants in the same contaminated area in Mae Sot with urinary Cd ≥ 5 μg/g Crea. In our own previous research, we found an imbalance in Ca reabsorption because of remarkable renal tubular dysfunction that leads to increased bone resorption markers in residents in Mae Sot aged ≥50 years old, particularly female residents including premenopausal women [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The study area and subjects have been previously described and extensively characterized (Nambunmee et al, 2010; Ruangyuttikarn et al, 2013). Briefly, the study participants consisted of 169 residents living in Mae Ku, Phra Thad Padang, and Mae Tao, known polluted areas of Mae Sot, and 100 participants living the Mae Kasa subdistrict, a non-contaminated area of Mae Sot (Simmons et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…These areas are all rural, with similar socioeconomic environments. Subjects from polluted areas aged ≥ 40 years and with urinary Cd levels ≥5 μg/g creatinine in the 2007 survey were included in this study (Nambunmee et al, 2010). Exposed residents were 5-year age-matched to residents from the Mae Kasa subdistrict.…”
Section: Methodsmentioning
confidence: 99%